PRE-EXTENSION DEMONSTRATION OF SHIRO TYPE FIELD PEA TECHNOLOGIES IN THE HIGHLANDS OF GUJI ZONE, OROMIA REGIONAL STATE, ETHIOPIA - Kebede, Basha; Bobo, Tekle; Korji, Dembi (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
Agricultural research centres have released wide varieties to improve field pea production. However, the productivity of field peas is low due to insufficient demonstration of released and adapted varieties at the farmers’ level. Hence, demonstrating released and improved varieties is the critical approval for large-scale production of field peas. Therefore, this experiment was exhibited at three highlands to estimate profitability and evaluate the yield of shiro-kind field pea varieties. The Bilalo variety was demonstrated with local varieties by 12 farmers in 2022. Yield and costs of production were collected. The data was analyzed through cost-benefit analysis and descriptive statistics. The result indicated that the Bilalo variety gave a better yield (25.92 Qt/ha) than the local variety (18.33 Qt/ha). Cost-benefit analysis indicated that the Bilalo variety gave better returns (108672 ETB/ha) than the local variety (54022 ETB/ha). Farmers prefer the Bilalo variety because it provides a higher harvest, is more disease tolerant and has a higher market value over the local variety. The improved Shiro field pea variety is significant for yield increment and profit growth. Thus, the Bilalo variety should be used for shiro-type field pea production in highland areas. Additional research is desirable to promote the Bilalo variety through scaling up in the highlands and similar agroecology of the Guji zone. JEL Classification Codes: Q16, O32, O13.